FAKTOR-FAKTOR KOMUNIKASI (YANG PERLU DIMILIKI) GENERASI Z DALAM MEMPERSIAPKAN KARIR - Ricky Marcelino Chandra; Michael Kurniawan Sudjianto; Erica Adriana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Many studies state that there are some of Generation Z who have a tendency to ignore the role of communication in dealing with the world of work. Currently, there are still several Generation Z during the Covid 19 pandemic, spending more of their time online and staying at home, which makes the role of communication ineffective and passive because communication is carried out virtually (Qurniawati and Nurohman, 2018). Generation Z characters who tend to communicate in a relaxed, open and friendly manner must be changed in good communication (Alyulistin, 2022).The purpose of this study is to provide an overview of whether the factors of the role of communication are in line with the personality of Generation Z who will prepare themselves to face the real world of work. The research method that will be used in this research is literature study which is an activity by collecting data through reading journals and recording them to be used as theory development (Rusmawan, 2019).The results of the study show that there are 7 communication support factors that are more dominant in influencing Generation Z, namely: Knowledge, Growth, Perception, Roles and Relationships, Emotions, Gender, and Environment.